A capacidade técnica para gestão na captação e execução de recursos recebidos por transferência voluntária nos municípios do Estado de São Paulo. - Pizzonia, Hellen Cristina Rubini Teixeira (Universidade Federal de São Carlos, 2025)
This study aims to verify the existence and technical capacity of management areas in São Paulo state municipalities regarding the capture, celebration, execution, and accountability of resources received through voluntary federal transfers. Having a technically capable management area is mandatory for municipalities to access these resources. The study analyzes factors influencing resource capture, main obstacles, and risks faced by municipal public managers. It will survey 36 São Paulo municipalities. The research proposal stems from the need to identify limitations and successful experiences in shaping management areas, their quality, and relation to increased municipal revenue.
The technical capacity for management in the capture and execution of resources received through voluntary transfers in the municipalities of the State of São Paulo
Keywords: Captação de recursos; Gestão pública; Gestão de projetos; Governança; Receitas públicas; Emendas parlamentares; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::CONTABILIDADE E FINANCAS PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::FINANCAS PUBLICAS INTERNAS